Concurrent, real-time and distributed programming in Java threads, RTSJ and RMI - Benmammar, Badr (Focus series, 2018)
This book provides an introduction to concurrent, real-time, distributed programming with Java object-oriented language support as an algorithm description tool. The book also contains an annex which contains a practical set of application exercises in relation to the theme of the book. Knowledge of the Java language is a prerequisite for understanding the book.